2018
DOI: 10.13031/trans.12804
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Intra-Event Phosphorus Dynamics in Drainage Water Using Phosphate Stable Oxygen Isotopes

Abstract: Quantifying fluxes and pathways of dissolved reactive phosphorus (DRP) in tile-drained landscapes has been hampered by a lack of in situ measurements that are sensitive to P fate and transport processes. One potential tool to help understand these dynamics is the oxygen isotope signature of phosphate ( 18 O PO4 ); however, its potential benefits and limitations are not well understood for intra-event dynamics at the field scale. The objectives of this study were to quantify intra-event variability of  18 O P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…Lastly, the lack of differences in P dynamics with response type may be the result of rapid connectivity between the surface and tiles that may in fact be found under the various response types. Indeed, Ford et al (2018) observed greater macropore flow contributions from clay soils in winter, when soils were wet. Kung et al (2000) also observed increased preferential flow into tile drains under wetter antecedent conditions and attributed this to the activation of mesopores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the lack of differences in P dynamics with response type may be the result of rapid connectivity between the surface and tiles that may in fact be found under the various response types. Indeed, Ford et al (2018) observed greater macropore flow contributions from clay soils in winter, when soils were wet. Kung et al (2000) also observed increased preferential flow into tile drains under wetter antecedent conditions and attributed this to the activation of mesopores.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of relationship between event response type and ratios of P concentrations between surface and tile may reflect the sampling frequency used (i.e., 2‐ to 8‐h‐interval samples for the Ontario sites; daily composites from 6‐h‐interval samples for the Ohio sites). Previous studies linking preferential flow to P loss in tiles used finer sampling resolutions (i.e., 5 min to 1 h; Williams et al, 2016, 2018; Ford et al, 2018) to capture rapid connectivity; however, such an intensive sampling frequency on the order of minutes throughout a 3‐yr study was not feasible. A second potential explanation for the lack of relationship between event response type and P mobilization in tile drainage may be related to the importance of P supply.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have quantified dissolved reactive P (DRP) loadings and have examined the mechanisms of DRP transport to subsurface drainage systems, less emphasis has been placed on other forms transported through tile drains, such as particulate P (PP) and dissolved unreactive P (Chen et al., 2018; Christianson, Harmel, Smith, Williams, & King, 2016; King et al., 2015; Radcliffe et al., 2015). In particular, as PP is lost from the landscape and delivered to downstream waterbodies, bioavailable P may be mobilized, promoting eutrophication and degradation of freshwater and marine sources or fueling in‐stream primary productivity (Brennan et al., 2017; Ford, Williams, Young, King, & Fischer, 2018; Zhu, Li, & Whelan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate concentration and subsequent leaching from the soil and epikarst zone have been found to control spring concentrations and loadings, whereas quickflow following storm events has been found to dilute concentrations relative to groundwater aquifer sources (Baran, Lepiller, & Mouvet, ; Husic, Fox, Ford, et al, and references within). Conversely, dissolved reactive phosphorus (DRP) has been found to be more concentrated in quickflow than in intermediate and slow flow pathways, stemming from agricultural management practices in which high soil P levels at the soil surface become connected to the stream network through macropores and overland flow during quickflow (Baker, Johnson, & Confesor, ; Ford, Williams, Young, King, & Fischer, ; Jarvie et al, ; King, Williams, & Fausey, ). Despite this, karst conduits have recently been recognized to be highly retentive of DRP, even during quickflow, because of transient sediment deposits within preferential pathways that adsorb or settle a portion of reactive P (Jarvie et al, ; Mellander et al, ).…”
Section: Introductionmentioning
confidence: 99%